2018
DOI: 10.21273/horttech04188-18
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Sprays of Silver Thiosulfate Produce Male Flowers on Female Hemp Plants

Abstract: Interest in hemp (Cannabis sativa) for its medicinal compounds, cannabidiol (CBD), and Δ-9-tetrahydrocannabidiol (THC), continues to increase. Maximizing yield of CBD and/or THC requires female plants because female inflorescences accumulate significantly greater concentrations of these compounds than male inflorescences. Production of all female seed requires induction of female plants to develop male flowers that produce genetically female pollen. Growers would like access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 23 publications
(27 reference statements)
4
66
0
1
Order By: Relevance
“…Silver nitrate inhibits ethylene action in plants (Kumar et al, 2009) and was reported to increase male sex expression in marijuana, cucumber and gourd plants (Atsmon and Tabbak, 1979;Ram and Sett, 1982;Stankovic and Prodanovic, 2002). In a recent study, applications of silver thiosulfate induced male flower formation on genetically female hemp plants (Lubell and Brand, 2018). These findings demonstrate that changes in growth regulator levels in treated plants can impact hermaphroditic flower formation.…”
Section: Discussionmentioning
confidence: 86%
“…Silver nitrate inhibits ethylene action in plants (Kumar et al, 2009) and was reported to increase male sex expression in marijuana, cucumber and gourd plants (Atsmon and Tabbak, 1979;Ram and Sett, 1982;Stankovic and Prodanovic, 2002). In a recent study, applications of silver thiosulfate induced male flower formation on genetically female hemp plants (Lubell and Brand, 2018). These findings demonstrate that changes in growth regulator levels in treated plants can impact hermaphroditic flower formation.…”
Section: Discussionmentioning
confidence: 86%
“…Beginning on 26 Sept. 2019, plants were provided short-day conditions of 12 h using a blackout curtain to initiate the flowering stage. Silver thiosulfate solution at a concentration of 3 mM was prepared according to Lubell and Brand (2018). Female plants were sprayed to runoff (400 mL/plant) on three occasions, 7 d apart, on 26 Sept., 3 Oct., and 10 Oct. 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Female plants can be masculinized by treatment with silver nitrate or silver thiosulfate (STS). Lubell and Brand (2018) demonstrated that foliar sprays of STS at 0.3 to 3 mM concentrations are effective for inducing male flowers on female plants. They noted that pollen output for masculinized female plants may be reduced compared with pollen output from genetically male plants.…”
mentioning
confidence: 99%
“…Factors such as altered hormones (Lubell & Brand, ; Ram & Jaiswal, ), daylength (Schaffner, ), and autosomal genes (Faux, Berhin, Dauguet, & Bertin, ) have been shown to influence sex expression. Through manipulation of hormones, it is possible to create all‐female progeny using pollen produced by a female (XX) plant induced to produce male flowers and pollen (Lubell & Brand, ). From a commercial perspective, these so‐called ‘feminized’ seeds are generally more expensive to produce than normal dioecious seeds due to the additional work required for their production and the market demand for all‐female seed lots.…”
Section: Introductionmentioning
confidence: 99%